Transition from 2D- to 3D-images: Modification of two-scale image model and image processing algorithms - Chochia, P. A. (Journal of communications technology & electronics, 2015)
The specificities of three-dimensional images are formulated. Application of the two-scale image model to 3D images is studied. Methods for modification of various image processing algorithms to 3D images are demonstrated.